低炭素Mn-Si鋼の初析フェライト変態初期における炭素の分配挙動に及ぼす合金元素の影響 - 山下, 孝子; 榎本, 正人; 松田, 広志; 奥田, 金晴; 田中, 裕二 (鉄と鋼, 2019)
Controlling carbon concentration and its distribution among constituent phases is one of the most important issues to achieve high strength and ductility in the design of steel. The carbon distribution near the α/γ interface at the early stage of isothermal holding at 750ºC was measured and visualized in Fe-C-Mn-Si alloys, containing 2 mass%Si and 1.5 or 2 mass%Mn, using recently developed high precision FE-EPMA, and results were compared with the theory of ferrite growth in multi-component low alloy steel. The carbon concentrations at α/γ interfaces in austenite were generally between the NPLE/PLE and paraequilbrium γ/(γ+α) boundary concentrations. In alloys of carbon content smaller than the NPLE/PLE boundary, it seems that α/γ interfaces migrated under the condition close to paraequilibrium or with partially developed spikes of alloy elements at early stages. On the other hand, in alloys of bulk composition on the boundary and its higher carbon concentration side, Mn enrichment was observed at the interfaces, and the carbon concentration tended to be higher than those in alloys of lesser carbon content, albeit there were variations at individual interfaces.